2012
DOI: 10.1111/j.1754-4505.2012.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of toothbrush design on the ability of nurses to brush the teeth of institutionalized cerebral palsy patients

Abstract: Brushing by nurses of cerebral palsy patients was more effective and instruction better retained with a triple-headed compared to single-headed toothbrush.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 10 publications
0
24
0
1
Order By: Relevance
“…), as did the hand search of the reference lists of the selected papers (Bloch‐Zupan & Maniere). Altogether, 15 eligible studies describing 18 comparisons were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…), as did the hand search of the reference lists of the selected papers (Bloch‐Zupan & Maniere). Altogether, 15 eligible studies describing 18 comparisons were included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that gingivitis is associated with poor oral hygiene, as demonstrated in previous studies [9,10], and that there is a biological gradient for the oral hygiene variable in individuals with developmental disabilities similar to that for dental caries [17]. Another study did not show this association [7].…”
Section: Discussionmentioning
confidence: 54%
“…The use of a visual examination without probing may have compromised the results, and the number of patients with gingivitis indicated by the records was likely lower than the actual number, as reported in a previous study based on gingival bleeding after brushing according to the Bass method [22]. The Modified Gingival Index was successfully used in a previous study of cerebral palsy patients [10]. Moreover, it is important to note that it is very difficult to perform reliable periodontal probing because there is no patient cooperation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations